Comportamiento agronómico de tres nuevos genotipos de algodón (Gossypium hirsutum L.) en el Sinú Medio. - Doria López, Edgardo; Ortega López, Arnulfo (Universidad de Córdoba -UNICORDOBA, 1992)
Algodón-Gossypium herbaceum